Measurement of the correlation between electron spin and photon linear polarization in atomic-field bremsstrahlung - Tashenov, Stanislav; Bäck, T.; Barday, R.; Cederwall, B.; Enders, J.; Khaplanov, A.; Poltoratska, Yu.; Schässburger, K.-U.; Surzhykov, Andrey (Physical review letters, 2011)
Atomic-field bremsstrahlung has been studied with a longitudinally polarized electron beam. The correlation between the initial orientation of the electron spin and the angle of photon polarization has been measured at the photon high energy tip region. In the time reversal this corresponds to a so-far unobserved phenomenon of production of longitudinally polarized electrons by photoionization of unpolarized atoms with linearly polarized photons. The results confirm the fully relativistic calculations for radiative recombination and suggest a new method for electron beam polarimetry.